Odpowiedzi

2010-03-07T19:11:42+01:00
H= -2 -27 = -29
g= -24 - 45= -69
f= -21 +14= -7
e= -5+5=0
d= -6 + 3= -3
b= -2 -15= -17
2010-03-07T19:14:42+01:00
H) (-18):9 - (-27):(-1) = -2 - 27 = -29
g) 6x(-4)+5x(-9) = -24 + (-45) = -24 - 45 = -69
f) 3x(-7)-7x(-2) = -21 - (-14) = -21 + 14 = -7
e) (-15):3-5x(-1) = -5 - (-5) = -5 + 5 = 0
d) 12:(-2)-(-3) = -6 + 3 = -3
b) -2-3x5 = -2 - 15 = -17
1 5 1
2010-03-07T19:17:43+01:00
H) (-18):9 - (-27):(-1)= -2- 27 = -29
6x(-4)+5x(-9)= -24x+ (-45x) = -69x
3x(-7)-7x(-2)= -21x+14x= -7x
(-15):3-5x(-1)= -5+5x
12:(-2)-(-3)= -6+3=-3
-2-3x5= -2-15x